Short- and Long-Run Analysis of Factors Affecting Electricity Consumption in Sub-Saharan Africa - Michieka, Nyakundi (International Journal of Energy Economics and Policy, 2015)
This paper explores the causal relationship between electricity consumption, gross domestic product (GDP), trade openness, financial development, and industry using a vector error correction model for five sub-Saharan countries. Results indicate that in the long run, all series exert an influence on electricity consumption in Cote d'ivioire and Zambia. Short run estimates reveal causality running from financial development and GDP to electricity consumption in Cote d'ivioire and South Africa. A modified version of Granger causality developed by Toda and Yamamoto (1995) found no causality in electric power consumption for Kenya. Since these countries differ economically, politically, and geographically, no universal policy implication can be surmised. Keywords: Electricity Consumption; Vector Error Correction Model; Sub-Saharan Africa JEL Classifications: C32, O13; O47; O55; Q43; Q48